2016
DOI: 10.1016/j.lindif.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Language development in rural and urban Russian-speaking children with and without developmental language disorder

Abstract: Using a newly developed Assessment of the Development of Russian Language (ORRIA), we investigated differences in language development between rural vs. urban Russian-speaking children (n = 100 with a mean age of 6.75) subdivided into groups with and without developmental language disorders. Using classical test theory and item response theory approaches, we found that while ORRIA displayed overall satisfactory psychometric properties, several of its items showed differential item functioning favoring rural ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
7
1
4
Order By: Relevance
“…Although rural areas are likely to be characterized by limited access to resources and services (Greenfield, 2009), which in turn has an indirect negative impact on children's language scores, in the current study, children in rural areas of the district performed better than their counterparts in urban areas. Our findings are in contrast with other studies that have reported overall better performance among children living in urban areas (Kornilova et al, 2017;Schady et al, 2015;Vogt et al, 2015). These findings may be attributed to the likelihood that the drawings on the KNT represented objects that were more familiar to children in rural areas than those living in urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Although rural areas are likely to be characterized by limited access to resources and services (Greenfield, 2009), which in turn has an indirect negative impact on children's language scores, in the current study, children in rural areas of the district performed better than their counterparts in urban areas. Our findings are in contrast with other studies that have reported overall better performance among children living in urban areas (Kornilova et al, 2017;Schady et al, 2015;Vogt et al, 2015). These findings may be attributed to the likelihood that the drawings on the KNT represented objects that were more familiar to children in rural areas than those living in urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…All children were monolingual speakers of Russian and had been independently diagnosed for DLD (in Russian, obščee nedorazvitie reči II-III urovnja ) based on a clinical evaluation by a multidisciplinary committee consisting of a speech pathologist, a psychiatrist, a neurologist, a pediatrician, and a clinical psychologist (cf. Kornilov et al, 2016). For privacy reasons we were not granted access to the diagnostic results.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, twenty‐three met criteria for DLD (age ranged from 7.33 to 15.25, M = 10.12, SD = 2.40; sixteen boys) and sixteen were classified as typically developing (TD; age ranged from 7.17 to 15.83, M = 11.14, SD = 2.18; seven boys). The language status classification was based on a set of expressive and receptive language measures obtained using a comprehensive standardized language development test in conjunction with a language sample analysis (see Kornilov et al., 2014, 2015, 2016; Rakhlin et al., 2013, for detailed descriptions). All children demonstrated normal hearing acuity by passing a bilateral hearing screening at 25 dB (500, 1000, 2000, and 4000 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…The narratives were analyzed and assigned scores or ratings (depending on the measure) for articulation quality, syntactic complexity, grammatical well‐formedness, semantic quality, and narrative structure (Rakhlin et al., 2013). The second was a standardized test developed to assess language development in Russian, which was previously shown to have psychometric properties (ORRIA; Kornilov et al., 2016), comparable to such established instruments as the clinical evaluation of language fundamentals (CELF) (Semel, Wiig, & Secord, 1995), test of language development (TOLD) (Newcomer & Hammill, 1982), and comprehensive assessment of spoken language (CASL) (Carrow‐Woolfolk, 1999). ORRIA is aimed at assessing a child's language development in the areas of morphology, syntax, compositional semantics, and lexicon in both receptive and expressive domains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation